(untitled) (Fiep Bulletin - online, 2013)
The growing number of cases of chronic diseases - NCDs, has raised concern about the factors that have led people to this situation.The objective of this study is to relate the risk factors associated with non-communicable chronic diseases to the lifestyle in individuals over 50 years of age, of both sexes. We evaluated a sample of 80 subjects (? 50 years) of both sexes, chosen intentionally. As a tool, we used an anamnese in order to identify data as physical activity level, presence or absence of pre-existing chronic diseases, and body mass index (BMI). An analysis of variance (ANOVA) was used to compare the results found with significant level of 5%. Regarding risk factors associated with NCD, prevailed: sedentarism (37.5%), obesity (18.7%) and smoking (11.2%). Women had a higher prevalence of physical inactivity (63.3%) and smoking (55.5%). Moreover, this studied showed increased presence of NCDs among females: 63.3%. When comparing genders, significant differences were observed when comparing the variable BMI between genders (p = 0.04) and smoking (p = 0.02). The study concluded that the lifestyle adopted by women who were part of the sample is associated with the presence of non-communicable chronic diseases. The control of risk factors contributed to reduce morbidity and mortality in this population, and improve the quality of life.